The Impact of the Sacred River Tourism on the Income of the People of Pasar Pedati Village, Pondok Kelapa District, Central Bengkulu Regency (Islamic Microeconomic Review) - Endah Zulsia Awwalisya; Desi Isnaini; Katra Pramadeka (Penerbit Jurnal Indonesia, 2023)
Sungai Suci is one of the tourist attractions in Bengkulu Province, Central Bengkulu Regency, to be precise in Pasar Pedati Village, Pondok Kelapa District, where this place is one of the places used by the local community as a livelihood (work) to meet their daily needs. The purpose of this study is to find out how the impact of the Holy River tourism on increasing people's income, especially in the Pasar Pedati Village area in an Islamic microeconomic review which consists of demand and supply, production theory, consumption theory, and buying and selling theory. The type of this research is field research (fried research) using a qualitative approach. From the results of the study it can be concluded that Sungai Suci tourism has a positive impact on several people in Pasar Pedati Village, who previously had no jobs and low income, now that they have opened a micro business in Sungai Suci tourism, they have additional income.